PENGARUH KUALITAS PRODUK, DESAIN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOTOR HONDA BEAT (Jurnal Bisnis Indonesia, 2022)
It is undeniable that technological advances are also felt in the automotive world. Technological advances in the automotive world can be seen by the many motorcycle manufacturers that produce motorized vehicles that have other advantages and advantages. The purpose of this study was to determine the effect of product quality, product design and price on purchasing decisions for Honda beat motorcycle products. The research method is to use a quantitative approach. The research conducted by the researcher refers to the use and measurement of the linkert scale which is calculated from 1 to 5. The number of samples used is 100 samples. This study uses descriptive analysis using Partial Least Square (PLS) and hypothesis testing using statistical methods supported by PLS 3.0 smart software. Based on the results of research that has been carried out by researchers, there are several conclusions. First, the results of this study have shown that there is a positive and significant influence between product quality variables on purchasing decisions. Second, the product design variable has a positive and significant influence on the purchasing decision variables. The three price variables have a positive and significant influence on the purchasing decision variables. DOI : https://doi.org/10.33005/jbi.v13i1.3075